2023
DOI: 10.1186/s12966-023-01414-4
|View full text |Cite
|
Sign up to set email alerts
|

Weather associations with physical activity, sedentary behaviour and sleep patterns of Australian adults: a longitudinal study with implications for climate change

Abstract: Background Weather is a potentially important influence on how time is allocated to sleep, sedentary behaviour and physical activity across the 24-h day. Extremes of weather (very hot, cold, windy or wet) can create undesirable, unsafe outdoor environments for exercise or active transport, impact the comfort of sleeping environments, and increase time indoors. This 13-month prospective cohort study explored associations between weather and 24-h movement behaviour patterns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…A previous study that analyzed the relationship between physical activity behavior and weather conditions using a wrist-worn Fitbit activity tracker over 13 months discovered that physical activity intensity played a crucial role in engaging in activity in adverse weather conditions. For instance, precipitation affected adults who partook in moderate to vigorous physical activity significantly more than those who partook in light physical activity [43]. This may be because weather conditions such as ice, snow, or severe cold would be more of an impediment for higher-intensity activities like running than for lower-intensity activities like walking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study that analyzed the relationship between physical activity behavior and weather conditions using a wrist-worn Fitbit activity tracker over 13 months discovered that physical activity intensity played a crucial role in engaging in activity in adverse weather conditions. For instance, precipitation affected adults who partook in moderate to vigorous physical activity significantly more than those who partook in light physical activity [43]. This may be because weather conditions such as ice, snow, or severe cold would be more of an impediment for higher-intensity activities like running than for lower-intensity activities like walking.…”
Section: Discussionmentioning
confidence: 99%
“…The improved accessibility and accuracy of weather forecasting through digital platforms and public broadcasting services and warnings help individuals make informed decisions about when to be active [24,45], which may have contributed to the lower impact of weather on their physical activity. In addition, Ferguson et al (2023) suggested that light physical activity is not significantly affected by extreme weather if proper clothing and equipment, such as an umbrella, are used to address the challenge [43]. The factors above highlight some of the significance of having effective adaptation strategies to cope with different weather conditions at the individual level [46].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, group-level work indicates that physical activity has associations with multiple factors, including, e.g., diet [78], gut microbiome [79], emotion regulation [80], fitness [81], weather [82], and metabolic [83] factors. Adding to group-level findings, studies using micro-longitudinal tracking and within-individual analyses have shown physical activity's associations with, e.g., sleep [84][85][86][87] and stress [88].…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation is that exclusion of those who did not wear the accelerometer for the required number of hours and days, resulted in under inclusion of data from older participants, so our estimates of MVPA may be higher than in the general population of mid-age adults. A third limitation is each participant provided a single week of data, and variability estimates may be different at different times of the year/in different seasons [ 29 , 30 ]. We also acknowledge that, because the accelerometers were not waterproof, we did not collect data during water-based activities, which may mean that estimates of acceleration, MVPA and/or variability were underestimated.…”
Section: Strengths and Limitationsmentioning
confidence: 99%